NATIONAL SEISMIC, RADAR AND SEISMOLOGICAL STUDIES OF SUBGLACIAL LAKE VOSTOK - S. V. Popov; V. N. Masolov; V. V. Lukin; A. M. Popkov (Лëд и снег, 2015)
The results of the remote sensing which carried out in the LakeVostokarea are discussed in the paper. A.P. Kapitsa and O.G. Sorokhtin started the geophysical researches in this area in 1950s. Satellite altimetry data, which analyzed in 1990s yielded to the discovering of the LakeVostok. After that, PMGE and RAE started the systematic studying of this natural phenomenon by seismic and radio-echo sounding. Total, 318 seismic soundings and 5190 kmof the radio-echo profiles has been collected by 2008. Special precise measurements which carried out in the 5G-1 borehole vicinity are resulted in the ice thickness over Vostok Station is 3760±30 mby seismic and 3775±15 mby radio-echo sounding. Thus, the error of geophysical measurements is less than 0.3%. The Russian investigations are resulted in definition the border of the lake, the discovering of 56 subglacial water caves around the lake and compilation the maps including ice thickness, ice base and bedrock topography and the depth of the lake. Average depth of the LakeVostokis about 400 m; water volume is 6100 km3. After 2008, the remote sensing works have been concentrated to the studying of the bottom sediments by refraction seismic technique. The firsts result shown that the bottom sediments thickness varies from 400 to1200 m.